1990
DOI: 10.1111/j.1348-0421.1990.tb01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Seroconversion of Antibody to Human T‐Cell Lymphotropic Virus Type‐I in Children of Okinawa, Japan

Abstract: From 1983 to 1986, 1,813 children in nursery schools in Ishigaki Island and 1,228 children under 15 years old in the rural area in the Yaeyama District of Okinawa, Japan. were tested for anti-HTLV-I, 18 children (1.0%) in Ishigaki Island and 39 children (3.2%) in the rural area were positive. In order to survey when anti-HTLV-I developed in these children, their older serum samples were investigated retrospectively for 1 to 5 years. Two cases of seroconversion from anti-HTLV-I negative to positive were found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In fact, recent genetic studies based on mitochondrial DNA indicated that only Pygmy-to-Bantu maternal gene flow occurred [38]. As HTLV-1 and -2 seem preferentially transmitted from men to women [4,39], such rare contacts are likely not to spread HTLVs outside the Pygmy community.…”
Section: Why Is the Level Of Htlv-1 And Htlv-2 Infection Much Higher mentioning
confidence: 99%
“…In fact, recent genetic studies based on mitochondrial DNA indicated that only Pygmy-to-Bantu maternal gene flow occurred [38]. As HTLV-1 and -2 seem preferentially transmitted from men to women [4,39], such rare contacts are likely not to spread HTLVs outside the Pygmy community.…”
Section: Why Is the Level Of Htlv-1 And Htlv-2 Infection Much Higher mentioning
confidence: 99%
“…Several investigators have described the presence of seronegative HTLV-I carriers (Saito et al, 1989;Kajiyama et al, 1990). Some HTLV-I carriers have been reported to be negative for serum anti-HTLV-I antibodies against viral structural proteins on screening examinations (Ehrlich et al, 1989).…”
mentioning
confidence: 99%